NF-kB and the CLL microenvironment - O’Donnell, Alice; Pepper, Chris; Mitchell, Simon; Pepper, Andrea (Frontiers in Oncology, 2023)
Chronic lymphocytic leukemia (CLL) is the most prevalent type of leukemia in the western world. Despite the positive clinical effects of new targeted therapies, CLL still remains an incurable and refractory disease and resistance to treatments are commonly encountered. The Nuclear Factor-Kappa B (NF-κB) transcription factor has been implicated in the pathology of CLL, with high levels of NF-κB associated with disease progression and drug resistance. This aberrant NF-κB activation can be caused by genetic mutations in the tumor cells and microenvironmental factors, which promote NF-κB signaling. Activation can be induced via two distinct pathways, the canonical and non-canonical pathway, which result in tumor cell proliferation, survival and drug resistance. Therefore, understanding how the CLL microenvironment drives NF-κB activation is important for deciphering how CLL cells evade treatment and may aid the development of novel targeting therapeutics. The CLL microenvironment is comprised of various cells, including nurse like cells, mesenchymal stromal cells, follicular dendritic cells and CD4+ T cells. By activating different receptors, including the B cell receptor and CD40, these cells cause overactivity of the canonical and non-canonical NF-κB pathways. Within this review, we will explore the different components of the CLL microenvironment that drive the NF-κB pathway, investigating how this knowledge is being translated in the development of new therapeutics.